Nanoentrepreneurship within the framework of Industry 5.0: an analysis based on the qualitative case study method - Canales-García, Rosa Azalea; Juárez Toledo, Rafael; Rojas Merced, Juvenal (Cooperativismo & Desarrollo, 2024)
Nano-entrepreneurships are businesses operated by individuals known as nano-entrepreneurs, who serve as pivotal actors within the Industry 5.0 framework. In contrast to traditional nano-entrepreneurs, schumpeterian nano-entrepreneurs are characterized by their adaptability, resilience in the face of environmental challenges, commitment to sustainability, and their capacity to foster cooperative relationships. This paper aims to analyze the integration of the schumpeterian nano-entrepreneur into Industry 5.0, conceptualized as a system rooted in cooperative relationships. To achieve this objective, we propose a theoretical-conceptual model referred to as the Nano-entrepreneur System, which seeks to identify the categories that connect the schumpeterian nano-entrepreneur to this context. Additionally, a qualitative case study is conducted in the city of Toluca, State of Mexico. The findings indicate that, although schumpeterian nano-entrepreneurships are managed by a single individual, they embody fundamental values aligned with the principles of the Social and Solidarity Economy, including collaboration and a commitment to generating social and economic impact.